Expansion power system transmission using ant colony optimization / Izzataswad Ibrahim - Ibrahim, Izzataswad (2015)
This thesis presents an application of ant colony optimization (ACO) to optimization the expansion transmission in power system. The main objective of this research is to find the lowest investment total cost in transmission network. This analysis are using at 24 bus reliability test system (RTS) for transmission expansion analysis, the results show, the ant colony optimization is capable to deliver a good solutions for relatively in large systems[l]. Ant colony optimization represent the behavior of ant, when the ants come out of their nest to find food, ants will leave their pheromone. Pheromone intended to make such as a track to came back again at nest[2], after take a long distance of trail the pheromone going evaporation with ambient temperature its make ants not interested to use that trail. Behavior of ant only attract and more interested at track have high pheromone intensity, high pheromone happen when too many ants through that trail [3] and high pheromone occurs at short distance of trail.